The Impact of Competency-Based Pedagogy on Students’ Motivation and Engagement: An Experimental Study - Mohzana Mohzana (Journal Emerging Technologies in Education, 2025)
Background. Competency-based pedagogy (CBP) has emerged as a transformative instructional approach aligned with 21st-century educational demands, emphasizing the mastery of specific skills and learner autonomy. Despite its increasing adoption, empirical evidence regarding its impact on student motivation and engagement remains limited, especially in higher education contexts. Purpose. This study aims to investigate the effect of CBP on students’ motivation and classroom engagement through an experimental design. Method. The research employed a quasi-experimental method with pretest-posttest control group design. Participants included 120 undergraduate students divided into experimental and control groups. The experimental group received instruction using CBP principles, while the control group followed a traditional teacher-centered model. Data were collected using validated motivation and engagement scales and analyzed using ANCOVA. Results. Findings indicated that students in the CBP group demonstrated significantly higher levels of intrinsic motivation and behavioral engagement compared to those in the control group (p < 0.05). The structured autonomy and performance-based assessment in CBP played a key role in enhancing learner interest and participation. Conclusion.This study concludes that competency-based pedagogy positively influences students’ motivational and engagement levels, supporting its integration into curriculum design to foster meaningful and active learning experiences.